A voxel-based morphometric study of age- and sex-related changes in white matter volume in the normal aging brain - Liu H; Wang L; Geng Z; Zhu Q; Song Z; Chang R; Lv H (Neuropsychiatric Disease and Treatment)
Haijing Liu*, Lixin Wang*, Zuojun Geng, Qingfeng Zhu, Zhenhu Song, Ruiting Chang, Huandi Lv Department of Radiology, Second Hospital of Hebei Medical University, Shijiazhuang, People’s Republic of China *These authors contributed equally to this work Objective: To carry out a cross-sectional study of 187 cognitively normal Chinese adults using the voxel-based morphometry (VBM) approach to delineate age-related changes in the white matter volume of regions of interest in the brain and further analyze their correlation with age. Materials and methods: A total of 187 cognitively normal adults were divided into the young, middle, and old age-groups. Conventional magnetic resonance imaging was performed with the Achieva 3.0 T system. Structural images were processed using VBM8 and statistical parametric mapping 8. Regions of interest were obtained by WFU PickAtlas, and all realigned images were spatially normalized. Results: Females showed significantly greater total white matter volume than males (t=2.36, P=0.0096, false-discovery rate [FDR] corrected). VBM demonstrated statistically significant age-related differences in white matter volume between the young age-group and the middle age-group (P<0.05, FDR corrected) and between the middle age-group and the old age-group (P<0.05, FDR corrected). No interaction was found between age and sex on white matter volume (P>0.05, FDR corrected). Logistic regression analysis revealed nonlinear correlation between total white matter volume and age (R2=0.124, P<0.001). White matter volume gradually increased before 40 years of age, peaked around 50 years of age, and rapidly declined after 60 years of age. Conclusion: Significant age-related differences are present in white matter volume across multiple brain regions during aging. The VBM approach may help differentiate underlying normal neurobiological aging changes of specific brain regions from neurodegenerative impairments. Keywords: brain, aging, magnetic resonance imaging, ROI, white matter volume, voxel-based morphometry